Estimation of Aflatoxin M1 Levels in Some Dairy Products Manufactured from Raw Milk Experimentally Inoculated with Toxin: H. S. Alnaemi - Alnaemi, H. S. (The Iraqi Journal of Veterinary Medicine, 2022)
Fate of AflatoxinM1 in soft white cheese and its by-product (whey) and in yogurt locally made from raw sheep’s and goat’s milk experimentally inoculated with 0.05 and 0.5 µg/l AflatoxinM1 were investigated using ELISA technique. Results reported that AflatoxinM1 was concentrated in cheese at levels significantly higher than that recorded in the raw milk that used for its processing, with a significant decrease in AflatoxinM1 levels in its by-product (whey) comparable to the raw milk used in manufacturing at both inoculated levels. Yogurt produced from raw sheep’s milk at second inoculated level exerted AflatoxinM1concentration significantly lower than that present in the milk. Significant differences in AflatoxinM1distribution in cheese and whey produced from sheep’s milk comparable to their counterparts produced from goat’s milk were recorded. Finally, results revealed the efficacious role of the various dairy manufacturing processes in AflatoxinM1 distribution and the necessity to issue of local legislations concerning the maximum permissible limits for AflatoxinM1 in milk in order to stay within the universal permissible levels for AflatoxinM1 in dairy products to provide greater protection for consumer health.